Physical Condition Analysis of Athetes of the Province of Kabupaten Sinjai - Ihsan, Andi; Fadlih, Andi Muhammad; Hasyim, Muhammad Qasash (Universitas Majalengka, 2024)
Sinjai and Bulukumba Regencies hosted the Provincial Sports Week (PORPROV) XVII, October 2022. This 4-yearly multi event competes and competes in 34 sports under the Sports Branch Management and KONI. The Government and Society of Sinjai Regency as one of the implementing hosts have planned to achieve successful achievements, successful implementation, economic success and administrative success and the target is to become the best 3rd rank from all districts and cities in South Sulawesi. The purpose of this study was to determine the physical condition of athletes consisting of components of speed, muscle strength, muscle power, flexibility, agility, muscle endurance and VO2max endurance for athletes in the sport of fencing, athletic measurable sports and karate martial arts for male and female athletes. The method used is descriptive quantitative by calculating the frequency and percentage to determine the level of physical condition category. This research was conducted from May to August 2022 by conducting tests and measurements of physical components in Sinjai Regency. The samples used were 65 male and female athletes from fencing, athletics and karate. Based on the results of data analysis and discussion, it is concluded that. The physical condition of speed, muscle strength, muscle power, flexibility, agility, muscle endurance and VO2max endurance for athletes in the sport of fencing, athletic measurable sports and karate martial arts for male and female athletes PORPROV XVII 2022, Sinjai Regency, the tendency is still at the moderate category level